2014
DOI: 10.18793/lcj2014.14.02
|View full text |Cite
|
Sign up to set email alerts
|

On being realistic about reducing the prevalence and impacts of youth sexual violence and abuse in two Australian Indigenous communities

Abstract: Social interventions, like medical ones, can produce negative as well as positive outcomes. It is important for policy and practice to learn what works, what doesn't work, and what produces unintended effects, for whom and in what contexts. This is the task of realist evaluation. The formulation and evaluation of programs aiming to deal with problems in Australian Aboriginal and Torres Strait Islander communities face a number of practical, conceptual and methodological problems. Here, realist methods for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Narrowing down the problem to a local context also provides a better opportunity for evaluation efforts to assess what works best for whom, in what conditions, and how. This is an iterative process, with a cycle of review and monitoring inbuilt to facilitate improvements in both program design and evaluation clarity (Pawson and Tilley 1997;Tilley et al 2014).…”
Section: Evaluate Outcomes and Disseminate New Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Narrowing down the problem to a local context also provides a better opportunity for evaluation efforts to assess what works best for whom, in what conditions, and how. This is an iterative process, with a cycle of review and monitoring inbuilt to facilitate improvements in both program design and evaluation clarity (Pawson and Tilley 1997;Tilley et al 2014).…”
Section: Evaluate Outcomes and Disseminate New Knowledgementioning
confidence: 99%
“…2 Situating place-based prevention on the global-local continuum framework has been adopted in the Neighbourhoods Project (Tilley et al 2014).…”
Section: Macromentioning
confidence: 99%
“…Thus, the level of risk, and contexts for risky behavior, may differ according to location. Such examination of “place” in the prevention of youth sexual violence and abuse is already occurring (see Rayment-McHugh, Adams, et al, 2015; Tilley et al, 2014), and it is recommended that future research consider more nuanced approaches that attend to some of the possible contextual risks and varying socioeconomic advantage, specific to the community itself, to extend existing offender-focused prevention initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding numerous methodological limitations, this research has generally found that treatment 'works' (Reitzel & Carbonell, 2006;Walker, McGovern, Poey & Otis, 2004). The more nuanced questions of what works, for which offenders, in what circumstances (Tilley et al, 2014) have been given much less attention. Exploring these questions is critical for the continual improvement of treatment programs and can provide guidance about potential changes that can be made to existing programs to improve practice and reduce recidivism.…”
mentioning
confidence: 97%